Assessment of Prescribing Patterns of Drugs in Chronic Kidney Disease Patients in a Tertiary Care Hospital - Tauro, Conrial Marion; Kamath, Jagadish V; Mishal, Mohammed; Hateefa, Zainabath (Journal of Pharmacy Practice and Community Medicine)
Introduction: A decrease in the Glomerular Reduction Rate, urinary abnormalities, or anatomical abnormalities of the renal tract are all signs of chronic kidney disease. Objectives: The main aim of our study is an assessment of prescribing patterns of drugs, patient comorbidities and risk factors associated with CKD. Materials and Methods: For six months, a retrospective observational study was carried out in a 700-bed multispecialty hospital. The statistical analysis was completed using Version 20 of the statistical package SPSS. [IBM SPASS statistics]. Results: Out of 99 patients included in the study, 76 were males and 23 were females. Majority of the patients were between the ages of 40 – 49, Only 7.1 percent of the patients were aged 20–29 years. Majority of the participants in the study were in the 40-49 year old age bracket. 89 patients were prescribed with anti-hypertensives,26 patients were prescribed with anti-diabetics, 57 patients were prescribed with anemic drugs,67 patients were prescribed with PPI’s,49 patients were prescribed with Diuretics. The most commonly occurring risk factors were found out to be Diabetes and High Blood Pressure. Conclusion: The most common pattern of prescription observed are anti-hypertensive Agents followed by anemic drugs. The number of patients involved in the study are having CKD stage 5 and associated with other comorbidities like hypertension, anemia, diabetes etc. Diabetes and high blood pressure are the two most common causes of chronic kidney disease, as well as the most common risk factors among CKD patients.
Keywords: Chronic kidney disease; Glomerulus filtration rate; Creatinine; Fluid intake; Prescribing patterns; Comorbidities; Risk factors